Influence of energy characteristics of surge arresters on their selection - Shevchenko, Sergey; Khlomko, Sergiy; Berchuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2017)
For analysis of thermal processes occurring in SA under conditions of presence of overvoltage of different nature in the electric network, it is necessary to conduct research using volt-ampere characteristics. Thus, energy, released in SA, has to be determined. This approach is essential for correct selection of parameters of SA not only in terms of protection of electrical networks, where it is installed, but also to provide proper operation of a protective device itself. This approach will allow choosing parameters of SA at a design stage, which greatly reduce emergency rate throughout the entire period of operation. Presented results of calculations show that at standard pulse of atmospheric overvoltage, SA maintains thermal balance at values of current of lightning of up to 75 kA. Design lightning currents for electrical networks are about 30 kA. However, it should be noted that this approach cannot be applied to the selection of SA in the assigned network, because it may be different in values of amplitudes of lightning currents, rates of increase and the number of lightning strikes in one channel (as we know, there may be 10 of them). All presented parameters will influence thermal balance of SA, and, at some values, they can lead to its disturbance, which will cause the failure of SA and the damage to equipment of electric network. This conclusion emphasizes the need for detailed analysis of overvoltage that may occur within the network when selecting parameters and the place of SA installation. Taking into account the magnitudes and composition of overvoltage will make it possible to provide serviceability of SA throughout the entire period of operation.